Singlet fission in self-assembled PDI nanocrystals. Issue 43 (17th September 2018) - Schierl, Christoph; Niazov-Elkan, Angelica; Shimon, Linda J. W.; Feldman, Yishay; Rybtchinski, Boris; Guldi, Dirk M.
Abstract : Upon photoexcitation, self-assembled PDI nanocrystals (S1 S0 ) in the form of rods of 70 nm width and 1 μm length are subject to a symmetry breaking charge separation (SBCS) as the first step in the singlet fission (SF) sequence. Abstract : Upon photoexcitation, self-assembled PDI nanocrystals (S1 S0 ) in the form of rods of 70 nm width and 1 μm length are subject to a symmetry breaking charge separation (SBCS) as the first step in the singlet fission (SF) sequence. Hereby, the correlated pair of triplet excited states 1 (T1 T1 ) is formed with a quantum yield of 122%. Decoherence and triplet diffusion within the nanocrystals affords a long-lived, uncorrelated pair of triplet excited states (T1 + T1 ) with a quantum yield of 24%.